"The relationship between the profits management and profits quality and their impact on users of accounting information (A comparative study of a sample of banks listed in the Iraqi market for securities) - مجيد محمد زهير; جاسم رؤى احمد (Journal of Economics and Administrative Sciences, 2019)
The aim of the research is to determine the impact of profit management practices on the quality of profits through the use of flexibility in determining accounting methods and practices profit information is one of the most important information that concerns current users in general and observing users in particular. Some corporations managements manipulate the results of the company’s profit or loss (income statement) and financial position statement with multiple reasons, including capital market motivations to raise their share prices in the stock market and attract investors, and on the other hand the motives of funding and borrowing loans, and the use of the flexibility in accounting policies and estimates to change the income figures (increase and decrease) that affects the disclosure process when preparing the financial statements which will be based on information for many of the misinformation and so that the loss of the most important characteristics of the quality of representation is sincere, which negatively affects the quality of accounting profits, the research community is listed the companies in the Iraqi market for securities, the sample of the research included a number of private banks listed in the Iraqi market for securities and the (5) banks are (Mosul Bank for Development and Investment, Ashur International Bank for investment, the Iraqi Investment Bank, the Iraqi National Bank , The Commercial Bank of Iraq), the search reached several results, the most important of which is that the profits quality in the banks of the sample of the research varies from one bank to another.